Variations on the death of a grandparent: an analysis of youth memoir. Issue 3 (5th May 2020) - Griffith, Jason J.; Amevuvor, Jocelyn
Abstract : Purpose: This paper aims to argue for the curricular inclusion of youth-generated young adult literature (YAL) alongside canonical literature and adult-generated YAL. The authors support this argument with the results of a qualitative analysis of youth memoir published in The Best Teen Writing. They strive to inform the debate between educators who value memoir as part of the secondary curriculum and critics who question the ability of youth to write purposeful, meaningful narrative. Additionally, the authors also present memoir as a unique genre for youth to document and process adolescence, and for youth to speak to issues which they deem important. Design/methodology/approach: Informed theoretically by the Youth Lens, which considers how texts reinforce and/or disrupt various figurations of adolescence and youth, this study uses a multistage qualitative analysis of 83 youth memoir published in nine volumes of the Best Teen Writing from 2010 to 2018. First, the authors conducted a Labovian plot analysis to consider what themes and topics were present as well as what this sample could teach us about youth. Next, they analyzed the sample for genre hallmarks specific to creative nonfiction and memoir to consider the question of quality of youth memoir. Findings: The findings suggest that there is no typical adolescence and that youth are balancing complex, intersectional identities, which they write about skillfully through memoir. These findings directly contrast with critics of youth memoir. Rather than clichéd, the memoirs the authors analyzed show youth as intercultural, capable of thoughtful reflection, capturing the transitory state of their youth (knowing they are not children anymore and lightly speculating about their future), skillfully integrating memoir genre hallmarks, and recording important events and perspectives with appeal to a broader readership. Furthermore, these findings position youth memoir as worthy of curricular inclusion alongside adult-generated YAL. Originality/value: If the critics of youth memoir are the loudest voices, youth memoir will be, at best, relegated as examples for writers rather than seen as valid additions to curricular canon. This work gives due credit to the quality of published youth memoir to showcase their potential for curricular and canonical addition. This study builds on smaller-scale case studies and personal accounts to make an argument for curricular inclusion of youth voices and youth memoir in the secondary canon.